Advancements in applicability of microbial fuel cell for energy recovery from human waste - Verma M.; Verma M.K.; Singh V.; Singh J.; Singh V.; Mishra V. (My University, 2025)
Microbial fuel cells (MFCs) technology is frequently conferred as a division of wastewater treatment along with electricity generation. Specifically, the application of MFCs for energy recovery from the waste is also great for waste management purpose. Designing bioelectric toilets with MFC technology is an idea to treat sewage wastewater along with disinfection for providing a viable solution for wastewater treatment. Treated water can be reused for toilet flushing after disinfection process, helping to reduce the demand of fresh water. Application of power management systems in MFC will open the possibilities for its real-world application for powering electronic gadgets. This review article encapsulates the discussion on human excreta as a substrate for the MFC attached septic tanks to improve waste management and energy recovery methods. Further, the discussion has been carried on the challenges in the scale-up of the MFC systems and its commercialization issues in the present work. © 2022 Elsevier Ltd